Battery diaphragm, preparation method thereof and aqueous sodium ion battery

By using carbon coated with modified coatings of sodium ferrocyanide, conductive agent and binder on the separator of aqueous sodium ion batteries, the problems of low conductivity and poor cycle stability are solved, and the battery energy is significantly improved Density and Coulomb efficiency achieve higher electrochemical performance.

CN119297535AActive Publication Date: 2025-01-10GUIZHOU WEIFANG ENERGY NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411508716.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-10
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

Aqueous sodium ion batteries have problems such as low interface conductivity, low reactivity, poor long cycle stability and low energy density, which limits their large-scale application.

Method used

The diaphragm matrix is ​​modified with carbon-coated sodium ferrocyanide, conductive agent and binder to form a high-performance battery separator, improving the cyclic stability, capacity and Coulomb efficiency of the battery.

Benefits of technology

Protect sodium ferrocyanide through carbon coating, optimize the electronic structure, adjust its release speed and conductivity, improve electrochemical performance, significantly improve the long cycle stability, capacity and energy density of the battery, and solve the problem of aqueous sodium ion batteries fast water dissolution and low interfacial conductivity problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297535A_ABST
    Figure CN119297535A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a diaphragm for a battery, a preparation method of the diaphragm and an aqueous sodium-ion battery. The battery diaphragm comprises a diaphragm substrate and a coating arranged on the diaphragm substrate, wherein the coating comprises carbon-coated sodium ferrocyanide, a conductive agent and a binder. The preparation method of the battery diaphragm comprises the following steps: mixing the carbon-coated sodium ferrocyanide, the conductive agent, the binder and the solvent to prepare slurry, coating the slurry on the diaphragm substrate, and drying to obtain the battery diaphragm. The high-performance battery diaphragm is obtained by arranging the modified coating containing the carbon-coated sodium ferrocyanide, the conductive agent and the binder on the conventional diaphragm substrate, and the diaphragm can improve the long cycle stability, the capacity, the coulombic efficiency and the energy density of the battery when being used for the water-based sodium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a battery diaphragm and a preparation method thereof, and an aqueous sodium ion battery. Background Art

[0002] Although lithium-ion batteries (LIBs) have been optimized to meet the requirements of portable electronic devices, some intrinsic properties make current LIBs less feasible for large-scale stationary ESSs, where cost, safety, and long cycle life are more important than energy density. One of the main issues is safety. The high risk of safety accidents in LIBs is due to flammable organic electrolytes and thermal runaway caused by the reactivity of electrode materials with electrolytes. In addition, the cost of lithium batteries is relatively high due to the special battery assembly technology, the need for a strictly dry environment during the manufacturing process, the high prices of transition metals, organic electrolytes, and lithium salts. The development of high-safety, low-cost, and long-cycle battery systems has become a current research hotspot.

[0003] Aqueous sodium-ion batteries perfectly meet the above requirements and are promising alternatives for large-scale applications. They can solve the safety issues of flammable organic electrolytes in traditional batteries and avoid strict manufacturing conditions. The prices of electrolyte solvents and salts are relatively low, and the ionic conductivity of aqueous electrolytes is 2 orders of magnitude higher than that of organic electrolytes. In addition, they are based on environmentally friendly aqueous electrolytes.

[0004] The most commonly used aqueous energy storage system abroad is the Prussian material symmetrical battery, but its poor cycle stability, low energy density, narrow voltage window and slow electrochemical power make it difficult to scale up aqueous sodium-ion batteries. Therefore, it is of great significance to develop a battery modified diaphragm that can contribute to the capacity of the battery itself and improve the cycle performance and coulombic efficiency to empower aqueous sodium-ion batteries.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The first purpose of the present invention is to provide a battery diaphragm to solve the technical problems of low interface conductivity, low reaction activity, poor long-cycle stability and low energy density of existing aqueous sodium ion batteries; a modification coating containing carbon-coated sodium ferrocyanide, a conductive agent and a binder is arranged on a conventional diaphragm substrate to modify the diaphragm substrate to obtain a high-performance battery diaphragm, which can be used in aqueous sodium ion batteries to improve the long-cycle stability, capacity, coulomb efficiency and energy density of the battery.

[0007] The second object of the present invention is to provide a method for preparing the battery separator as described above, which has a simple preparation process, controllable thickness of the modified layer, and is easy to achieve mass production.

[0008] A third object of the present invention is to provide an aqueous sodium ion battery comprising the battery separator as described above.

[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0010] A battery diaphragm comprises a diaphragm substrate and a coating arranged on the diaphragm substrate, wherein the coating comprises carbon-coated sodium ferrocyanide, a conductive agent and a binder.

[0011] Preferably, the carbon-coated sodium ferrocyanide is double-layer carbon-coated sodium ferrocyanide, comprising sodium ferrocyanide and a first carbon layer and a second carbon layer sequentially coated on the outside of the sodium ferrocyanide.

[0012] Preferably, the carbon source for forming the first carbon layer includes at least one of polyvinyl alcohol, glacial acetic acid, tannic acid and oxalic acid.

[0013] Preferably, the carbon source for forming the second carbon layer includes sorbitan monooleate polyoxyethylene ether.

[0014] Preferably, the method for preparing the carbon-coated sodium ferrocyanide comprises the following steps:

[0015] Sodium ferrocyanide is mixed with the carbon source of the first carbon layer, ethanol is added dropwise for grinding, and the material after grinding is subjected to a first drying treatment. The material after the first drying treatment is then mixed with the carbon source of the second carbon layer, ethanol is added dropwise for grinding, and the material after grinding is subjected to a second drying treatment. The material after the second drying treatment is carbonized under an inert atmosphere to obtain double-layer carbon-coated anhydrous sodium ferrocyanide.

[0016] Preferably, the sodium ferrocyanide is anhydrous sodium ferrocyanide obtained by grinding and drying sodium ferrocyanide decahydrate;

[0017] The mass ratio of the carbon source of the first carbon layer to the anhydrous sodium ferrocyanide is 2%-8%; and / or the mass ratio of the carbon source of the second carbon layer to the anhydrous sodium ferrocyanide is 1%-5%.

[0018] Preferably, the temperature of the carbonization treatment is 260-300° C., and the time of the carbonization treatment is 6-10 h.

[0019] Preferably, in terms of mass percentage, the coating comprises 70%-90% of the carbon-coated sodium ferrocyanide, 5%-20% of the conductive agent and 5%-10% of the binder.

[0020] Preferably, the binder comprises PVDF and / or CMC.

[0021] Preferably, the coating has a thickness of 5-30 μm.

[0022] A method for preparing the battery separator as described above comprises the following steps:

[0023] The carbon-coated sodium ferrocyanide, a conductive agent, a binder and a solvent are mixed to form a slurry, which is then coated on a diaphragm substrate and dried to obtain the slurry.

[0024] An aqueous sodium ion battery comprises the battery separator as described above.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) The present invention modifies the diaphragm substrate by using a modification coating containing carbon-coated sodium ferrocyanide, a conductive agent and a binder. Sodium ferrocyanide can be used to in-situ adjust the coordinated metal ions to improve the specific capacity and cycle performance. However, since sodium ferrocyanide is water-soluble, conventional methods of directly attaching sodium ferrocyanide to the diaphragm substrate often cause a large amount of loss of the modified material. The present invention uses carbon-coated sodium ferrocyanide for modification, which protects the internal substance while optimizing the electronic structure. The release rate and conductivity of sodium ferrocyanide can be adjusted in situ, thereby avoiding the loss of sodium ferrocyanide due to dissolution and improving the electrochemical performance.

[0027] (2) The modified coating of the present invention contains a conductive agent and a binder. The conductive agent increases the ion transmission efficiency and the electronic conductivity; the binder allows the sodium ferrocyanide to contact the diaphragm matrix more closely, slowing down its loss and increasing the long cycle performance.

[0028] (3) The aqueous sodium ion battery provided by the present invention has good long-cycle stability, large capacity, high coulombic efficiency and energy density, which solves the problem of rapid water dissolution of sodium ferrocyanide, as well as the problems of low interface conductivity, low reaction activity, poor long-cycle stability and low energy density of traditional aqueous sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 The full battery assembled with the diaphragm prepared in Example 1 of the present invention is 0.2Ag -1 The charge and discharge curves of the 98th to 100th cycles under the current density;

[0031] Figure 2The full battery assembled with the diaphragm prepared in Example 17 of the present invention is 0.2Ag -1 The charge and discharge curves of the 98th to 100th cycles under the current density. DETAILED DESCRIPTION

[0032] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0033] A first aspect of the present invention provides a battery separator, comprising a separator substrate and a coating disposed on the separator substrate, wherein the coating comprises carbon-coated sodium ferrocyanide, a conductive agent and a binder.

[0034] The present invention uses coated modified sodium ferrocyanide with a conductive agent and a binder to modify a diaphragm substrate, and forms an interface modified conductive layer on the diaphragm substrate, thereby solving the problem of rapid water dissolution of sodium ferrocyanide, as well as the problems of low interface conductivity, low reaction activity, poor long cycle stability and low energy density of traditional aqueous sodium ion batteries.

[0035] Sodium ferrocyanide can regulate the coordinated metal ions in situ, and enhance the crystal structure stability of Prussian positive electrode materials during discharge. However, since sodium ferrocyanide is water-soluble, conventional adsorption modification methods often cause a large amount of sodium ferrocyanide loss. Sodium ferrocyanide is released quickly in the early stage, with a large capacity growth rate, but unstable in the middle and late cycles. Therefore, the present invention uses a multi-porous structure obtained by carbon coating and sodium ferrocyanide modified with multiple active groups to modify the diaphragm matrix. The carbon coating layer structure protects the internal material while optimizing the electronic structure, enhancing the electron migration ability, and can regulate the release rate of sodium ferrocyanide during charging and discharging by adjusting the carbon content, and regulate the release rate and conductivity of sodium ferrocyanide in situ. The slowly released sodium ferrocyanide can effectively prevent the capacity reduction caused by the Jiang-Taylor effect caused by the dissolution of transition metal ions in the Prussian blue analog material, and increase the long cycle capacity.

[0036] The interface modified by carbon-coated sodium ferrocyanide, conductive agent and binder can form an interface modified conductive layer, increase ion mobility and electronic conductivity, enhance the adhesion of the modified material, and effectively reduce the loss of the modified material (sodium ferrocyanide). Under the action of the in-situ interface conductive layer, the water decomposition problem in the aqueous electrolyte can be effectively prevented, and the decomposed H + Will move to the Fe(CN)6-rich 4- The obtained membrane has good wettability, and the conductive agent and binder are rich in multi-electron structures, which are conducive to the rapid passage of ions and the rapid migration of electrons.

[0037] In some specific embodiments of the present invention, the carbon-coated sodium ferrocyanide used is double-layer carbon-coated sodium ferrocyanide, including sodium ferrocyanide and a first carbon layer and a second carbon layer sequentially coated on the outside of the sodium ferrocyanide.

[0038] In some specific embodiments of the present invention, the carbon source used to form the first carbon layer includes at least one of polyvinyl alcohol, glacial acetic acid, tannic acid and oxalic acid.

[0039] The carbon source used to form the first carbon layer of the present invention has a low decomposition temperature, which can achieve low-temperature carbonization and avoid the decomposition of sodium ferrocyanide. The coated raw material will etch the cathode material and slightly etch the sodium ferrocyanide. During low-temperature carbonization, a contact interface with a deeper fit layer is formed, which is rich in functional groups and is conducive to electron adsorption and ion escape.

[0040] In some specific embodiments of the present invention, the carbon source used to form the second carbon layer includes sorbitan monooleate polyoxyethylene ether. The outer carbon layer (second carbon layer) can optimize the pore structure, further optimize the spatial cage effect, and is rich in functional group structure, which is conducive to increasing the cycle stability.

[0041] The carbon source of the second carbon layer is polyoxyethylene sorbitan monooleate, which is a non-ionic surfactant with good emulsifying effect and a wide spatial occupancy. Its introduction can increase the carbon layer spacing during carbonization, thereby further enriching the pore structure, and its surface is rich in active groups. The introduction of C=O bonds, COC bonds and other bonds will not be lost due to high temperature when low-temperature cracking is adopted, and a large number of active groups are retained, which increases its surface charge distribution and optimizes the electron transmission channel. During carbonization, it covers the surface of the first carbon layer to form a second carbon layer, forming a double carbon layer structure, which optimizes the pore structure while further stabilizing the internal space.

[0042] In some specific embodiments of the present invention, the method for preparing the carbon-coated sodium ferrocyanide comprises the following steps:

[0043] Sodium ferrocyanide is mixed with the carbon source of the first carbon layer, ethanol is added dropwise for grinding, and the material subjected to the first drying treatment is mixed with the carbon source of the second carbon layer, ethanol is added dropwise for grinding, and the material subjected to the second drying treatment is subjected to a carbonization treatment under an inert atmosphere to obtain anhydrous sodium ferrocyanide coated with a double-layer carbon. The coating means of sodium ferrocyanide of the present invention is simple, and the conditions are mild and controllable.

[0044] In some specific embodiments of the present invention, the sodium ferrocyanide used for carbon coating is anhydrous sodium ferrocyanide obtained by grinding and drying sodium ferrocyanide decahydrate;

[0045] The mass ratio of the carbon source of the first carbon layer used to the anhydrous sodium ferrocyanide is 2%-8%, for example, it can be any point value among 2%, 3%, 4%, 5%, 6%, 7%, and 8%, or a range value consisting of any two point values; and / or, the mass ratio of the carbon source of the second carbon layer used to the anhydrous sodium ferrocyanide is 1%-5%, for example, it can be any point value among 1%, 2%, 3%, 4%, and 5%, or a range value consisting of any two point values.

[0046] The amount of sorbitan monooleate polyoxyethylene ether, the carbon source of the second carbon layer, is too small to optimize the pore structure. Too much sorbitan monooleate polyoxyethylene ether will react with sodium ferrocyanide to generate byproducts such as Na2O.

[0047] In some specific embodiments of the present invention, the temperature of the carbonization treatment is 260-300°C, for example, it can be any point value among 260°C, 270°C, 280°C, 290°C, and 300°C, or a range value consisting of any two point values; the time of the carbonization treatment is 6-10h, for example, it can be any point value among 6h, 7h, 8h, 9h, and 10h, or a range value consisting of any two point values.

[0048] Since the decomposition temperature of sodium ferrocyanide is 435°C, the present invention adopts a carbon source that can be cracked at low temperature to coat the sodium ferrocyanide. After low-temperature carbonization coating treatment at 260-300°C, sodium ferrocyanide modified with a multi-porous structure / multi-active groups can be obtained, and a double carbon layer structure is formed to protect the internal substance while optimizing the electronic structure, enhancing the electron migration ability, and can in-situ adjust the release rate and conductivity of sodium ferrocyanide.

[0049] In some specific embodiments of the present invention, the coating includes 70%-90% carbon-coated sodium ferrocyanide, 5%-20% conductive agent and 5%-10% binder by mass percentage. If the content of carbon-coated sodium ferrocyanide is too high, the concentration of conductive agent is low and the conductivity is poor; if the content of carbon-coated sodium ferrocyanide is too low, the cycle stability of the battery will be affected.

[0050] In some embodiments, typically but not limiting, for example, the mass percentage of carbon-coated sodium ferrocyanide in the coating can be any point value among 70%, 75%, 80%, 85%, 90%, or a range value consisting of any two point values; the mass percentage of the conductive agent in the coating can be any point value among 5%, 10%, 15%, 20%, or a range value consisting of any two point values; the mass percentage of the binder in the coating can be any point value among 5%, 6%, 7%, 8%, 9%, 10%, or a range value consisting of any two point values.

[0051] In some specific embodiments of the present invention, the conductive agent used may be conductive carbon black.

[0052] In some specific embodiments of the present invention, the binder used includes PVDF and / or CMC.

[0053] In some specific embodiments of the present invention, the thickness of the coating is 5-30 μm, for example, it can be any value among 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, or a range consisting of any two values.

[0054] In some specific embodiments of the present invention, the membrane matrix includes any one of a glass fiber membrane, a cellulose membrane, a PP membrane and a PE membrane.

[0055] A second aspect of the present invention provides a method for preparing a battery separator according to any one of the aforementioned embodiments, comprising the following steps:

[0056] The carbon-coated sodium ferrocyanide, a conductive agent, a binder and a solvent are mixed to form a slurry, which is then coated on a diaphragm substrate and dried to obtain the slurry.

[0057] The method of the invention has simple preparation process, low cost, controllable coating thickness, and can quantitatively adjust the thickness of the modified coating layer, thereby adjusting the content of the modified substance.

[0058] In the present invention, the drying conditions are not specifically limited, and are subject to complete evaporation of the solvent, and technicians can select them according to their needs.

[0059] A third aspect of the present invention provides an aqueous sodium ion battery, comprising the battery separator described in any one of the aforementioned embodiments, or a separator produced by the method for preparing the battery separator described in the aforementioned embodiments.

[0060] In some specific embodiments of the present invention, the aqueous sodium ion battery further comprises a positive electrode sheet, and the positive electrode active material for the positive electrode sheet comprises a Prussian blue analogue. As an example, the positive electrode active material may be a manganese-based Prussian white material.

[0061] In some specific embodiments of the present invention, the aqueous sodium ion battery further comprises a negative electrode sheet, and the negative electrode active material for the negative electrode sheet may be a sodium titanium phosphate negative electrode material.

[0062] In some specific embodiments of the present invention, the electrolyte of the aqueous sodium ion battery uses a 17M NaClO4 aqueous solution as the aqueous electrolyte.

[0063] The following is a detailed description of some embodiments of the present invention in conjunction with specific examples. The raw materials used in the examples can be purchased from the market unless otherwise specified.

[0064] Example 1

[0065] S1. Preparation of Carbon-coated Sodium Ferrocyanide

[0066] Take 5g of sodium ferrocyanide decahydrate, ball-mill it to about 10 microns (600r / min, 2h), dry it at 100℃ for 24h, remove the crystal water, take it out immediately, grind and mix it with polyvinyl alcohol, the amount of polyvinyl alcohol is 5% of the mass of anhydrous sodium ferrocyanide, add ethanol to grind it evenly, and dry it at 60℃; then grind and mix it with anhydrous sorbitan monooleate polyoxyethylene ether, the amount of anhydrous sorbitan monooleate polyoxyethylene ether is 3% of the mass of anhydrous sodium ferrocyanide, add ethanol to grind it evenly, and dry it at 60℃, take out the powder and place it in a tubular furnace, and carbonize it at 280℃ for 8h under an argon atmosphere to obtain anhydrous sodium ferrocyanide coated with a double carbon layer.

[0067] S2. Preparation of battery separator

[0068] A glass fiber diaphragm is used as the diaphragm matrix. The double-layer carbon-coated anhydrous sodium ferrocyanide, conductive carbon black and PVDF prepared in this embodiment are taken in a mass ratio of 8:1:1, and NMP is added to prepare a black slurry. The slurry is then coated on a glass fiber diaphragm with a thickness of 260 μm using a scraper to a coating thickness of 10 μm. The slurry is then vacuum dried at 120°C for 12 hours to obtain the battery diaphragm.

[0069] Example 2

[0070] Example 2 is similar to Example 1, except that in step S1, polyvinyl alcohol is replaced with an equal amount of glacial acetic acid, and the other conditions are the same as those in Example 1.

[0071] Example 3

[0072] Example 3 is similar to Example 1, with the only difference being that in step S1, polyvinyl alcohol is replaced with an equal amount of tannic acid, and the other conditions are the same as those in Example 1.

[0073] Example 4

[0074] Example 4 is similar to Example 1, with the only difference being that in step S1, polyvinyl alcohol is replaced with an equal amount of oxalic acid, and the other conditions are the same as those in Example 1.

[0075] Example 5

[0076] Example 5 is similar to Example 1, with the only difference being that in step S1, the amount of sorbitan monooleate polyoxyethylene ether is 1% of the mass of anhydrous sodium ferrocyanide, and the other conditions are the same as those in Example 1.

[0077] Example 6

[0078] Example 6 is similar to Example 1, except that in step S1, polyvinyl alcohol is replaced with an equal amount of sorbitan monooleate polyoxyethylene ether, and the other conditions are the same as those in Example 1.

[0079] Example 7

[0080] Example 7 is similar to Example 1, with the only difference being that in step S1, the amount of polyvinyl alcohol is changed to 2% of the mass of anhydrous sodium ferrocyanide, and the other conditions are the same as those in Example 1.

[0081] Example 8

[0082] Example 8 is similar to Example 1, with the only difference being that in step S1, the amount of polyvinyl alcohol is changed to 8% of the mass of anhydrous sodium ferrocyanide, and the other conditions are the same as those in Example 1.

[0083] Example 9

[0084] Example 9 is similar to Example 1, with the only difference being that in step S2, the coating thickness is changed to 5 μm, and the other conditions are the same as those in Example 1.

[0085] Example 10

[0086] Example 10 is similar to Example 1, with the only difference being that in step S2, the coating thickness is changed to 15 μm, and the other conditions are the same as those in Example 1.

[0087] Embodiment 11

[0088] Example 11 is similar to Example 1, with the only difference being that in step S1, the carbonization time is changed to 10 h, and the other conditions are the same as those in Example 1.

[0089] Example 12

[0090] Example 12 is similar to Example 1, with the only difference being that in step S1, the carbonization time is changed to 6 hours, and the other conditions are the same as those in Example 1.

[0091] Example 13

[0092] Example 13 is similar to Example 1, with the only difference being that in step S1, the carbonization temperature is changed to 260°C, and the other conditions are the same as those in Example 1.

[0093] Embodiment 14

[0094] Example 14 is similar to Example 1, with the only difference being that in step S1, the carbonization temperature is changed to 300°C, and the other conditions are the same as those in Example 1.

[0095] Embodiment 15

[0096] Example 15 is similar to Example 1, with the only difference being that in step S2, the mass ratio of double-layer carbon-coated anhydrous sodium ferrocyanide, conductive carbon black and PVDF is changed to 9:0.5:0.5, and the other conditions are the same as those in Example 1.

[0097] Example 16

[0098] Example 16 is similar to Example 1, with the only difference being that in step S2, the mass ratio of double-layer carbon-coated anhydrous sodium ferrocyanide, conductive carbon black and PVDF is changed to 7:2:1, and the other conditions are the same as those in Example 1.

[0099] Embodiment 17

[0100] Example 17 is similar to Example 1, with the only difference being that in step S2, PVDF is replaced with an equal amount of CMC, and the other conditions are the same as those in Example 1.

[0101] Comparative Example 1

[0102] The diaphragm in Comparative Example 1 is the diaphragm substrate in Example 1 (260 μm glass fiber diaphragm), without any modification coating.

[0103] Comparative Example 2

[0104] Comparative Example 2 is similar to Example 1, except that in step S2, an equal amount of sodium ferrocyanide decahydrate is used instead of anhydrous sodium ferrocyanide coated with double-layer carbon. The preparation method of the battery separator is the same as that of Example 1, that is, the sodium ferrocyanide in this comparative example is not coated. The specific steps are as follows:

[0105] A glass fiber diaphragm is used as a diaphragm matrix, and sodium ferrocyanide decahydrate, conductive carbon black and PVDF are taken in a mass ratio of 8:1:1, and NMP is added to prepare a black slurry, which is then coated on a glass fiber diaphragm with a thickness of 260 μm using a scraper to a coating thickness of 10 μm, and then vacuum dried at 120° C. for 12 hours to obtain the battery diaphragm.

[0106] Comparative Example 3

[0107] A 260 μm glass fiber diaphragm was used as the diaphragm matrix, and the diaphragm matrix was modified directly by an infiltration process using unmodified sodium ferrocyanide, and the steps were as follows:

[0108] A 0.5 M sodium ferrocyanide solution was evenly dripped onto the glass fiber diaphragm using a pipette for infiltration. The amount of sodium ferrocyanide used was the same as that in Example 1. The membrane was dried at 60° C. for 2 h and at 120° C. for 12 h.

[0109] Test example

[0110] The membranes prepared in each embodiment and each comparative example were respectively used to assemble aqueous sodium ion batteries and the electrochemical performance tests were performed. The battery assembly process and test conditions were as follows:

[0111] Preparation of positive electrode active material: 5mmol of Mn salt and 25mmol of trisodium citrate were dissolved in 50ml of deionized water to obtain solution A; 5mmol of Na4Fe(CN)6 10H2O and 25mmol of trisodium citrate were dissolved in 50ml of deionized water to obtain solution B; solution A was added dropwise to solution B, and stirring was continued for 16h, and then aged for 24h. Then, the solution was filtered and washed with ethanol once to obtain a solid Mn-based Prussian blue analogue, which was vacuum dried at 120℃ for 30h and ground to obtain a powder material.

[0112] Preparation of positive electrode sheet: Take the positive electrode active material prepared by the above method, PVDF (polyvinylidene fluoride), and conductive carbon black in a mass ratio of 8:1:1, weigh the above materials according to the proportion and place them in a small weighing bottle (2.5cm*2.5cm), add NMP (N-methylpyrrolidone) solution, stir for 4 hours, apply the stirred slurry on stainless steel foil, place it in a vacuum drying oven after coating, dry it for 8 hours, and then use a cutting machine to cut it into small disc electrode sheets with a diameter of 16mm, and compact it under a pressure of 10Mpa. Ensure that the mass of the Prussian blue analog active substance on this electrode is about 2.5-3mg cm -2 , thereby obtaining the positive electrode of the button battery.

[0113] Preparation of negative electrode active material: Sodium titanium phosphate negative electrode material is selected, and the preparation steps are as follows: 1.0g NaH2PO2, 1.0g H2TiO3 and 1.0g H3PO4 are added to 1.0ml deionized water, stirred at 800r / min for 5min to mix evenly, transferred to a 50ml high-pressure reactor, kept at 140℃ for 8h, the heating rate is 5℃ / min, centrifuged to obtain a white precipitate, dried overnight at 60℃ in a vacuum drying oven to obtain NaTi2(PO4)3 precursor. 1.0g of the prepared NaTi2(PO4)3 precursor and 0.05g of glucose are put into a mortar, and 5ml of anhydrous ethanol solution is taken for grinding for 10min. Then transfer to a ball mill jar, ball mill for 60min, take out the powder, place it in a vacuum drying oven, dry it, heat it to 650℃ at 5℃ / min and carbonize it for 2h to obtain a carbon-coated NaTi2(PO4)3 negative electrode active material.

[0114] Preparation of negative electrode sheet: Take the negative electrode active material, conductive carbon black, and PVDF (polyvinylidene fluoride) prepared by the above method, with a mass ratio of 7:2:1, weigh the above materials according to the proportion and place them in a small weighing bottle (2.5cm*2.5cm), add 17 drops of NMP (N-methylpyrrolidone) solution, stir for 4 hours, apply the stirred slurry on copper foil, place it in a vacuum drying oven after coating, dry it for 8 hours, and then use a cutting machine to cut it into small disc electrode sheets with a diameter of 16mm, and compact it under a pressure of 5Mpa. Ensure that the mass of the active material on this electrode is about 2.5-3.6mg cm -2 , ensure that the positive and negative electrode capacity ratio is between 1:(1.2-2.0).

[0115] Electrolyte: 17M NaClO4 aqueous solution was used as the aqueous electrolyte.

[0116] Full battery assembly: The full battery uses 2025 button cells, and the installation order is negative electrode shell, spring, gasket, negative electrode plate, electrolyte, diaphragm (diaphragm prepared in each embodiment and each comparative example), electrolyte, positive electrode plate, gasket, positive electrode shell; the mass ratio of positive and negative active materials is about 1:1.2. The mass of positive active material is about 2.5-3mg / cm 2 .

[0117] Full battery test: A charge and discharge cycle test was performed on a full battery assembled with the battery diaphragms prepared in each embodiment and each comparative example on a Newwell battery test system. The test voltage range was 0.01-2.0V, the test current density was 0.2A / g, and the temperature was kept constant at 25°C. The capacity attenuation rate of the 100th to 2000th cycles was obtained by subtracting the specific capacity of the 2000th cycle from the specific capacity of the 100th cycle and then dividing it by the specific capacity of the 100th cycle. The results are shown in Table 1.

[0118] Table 1

[0119]

[0120]

[0121] It can be seen from the data in Table 1 that the electrochemical performance of the modified diaphragm with double-layer carbon coating is relatively stable, with less attenuation during the cycle of 100-2000 cycles. The effect of single-layer coating is obviously not as good as that of double-layer coating. In addition, the appropriate thickness will affect the overall electrochemical performance. When the coating thickness is reduced, the electrochemical performance of the material decreases. When the coating thickness is too thick, the electrochemical performance of the material will also decrease. The reason is that the amount of sodium ferrocyanide is too small, resulting in poor repair effect. The reason for being too thick is that the thickness will affect the ion transmission efficiency and reduce the conductivity. In addition, the carbonization temperature and time will affect the coating effect. The appropriate carbonization temperature can obtain a uniform carbon layer thickness and a suitable pore structure. Too low carbonization temperature or too little time will result in incomplete carbonization. Too high carbonization temperature or too long time will result in excessive carbonization and disappearance of multi-functional group activity. Obviously, under the uncoated diaphragm, the electrochemical performance is extremely unstable, which is caused by the lack of sodium ferrocyanide repair. After the binder was replaced with CMC, the long cycle performance decreased. This is because CMC is water-soluble, which is not conducive to long-term adhesion. When uncoated sodium ferrocyanide was used, the effect was not good. This was due to the large amount of sodium ferrocyanide dissolved. In addition, the diaphragm modified by the dripping method of 0.5M sodium ferrocyanide showed an increase in specific capacity at the beginning, but the long-term stability was poor. This was also caused by the dissolution of sodium ferrocyanide and the deterioration of the repair effect.

[0122] Depend on Figure 1 and Figure 2 It can be seen that the charge and discharge curves of the modified diaphragm are well matched and basically overlap, indicating that its electrochemical reaction stability is excellent, but the Figure 2 There is no obvious voltage platform around 0.9 V, which is related to the dissolution of CMC in water. After dissolution, its repair effect gradually deteriorates.

[0123] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.

Claims

1. A battery separator, characterized in that: The invention comprises a diaphragm substrate and a coating arranged on the diaphragm substrate, wherein the coating comprises carbon-coated sodium ferrocyanide, a conductive agent and a binder.

2. The battery separator according to claim 1, characterized in that The carbon-coated sodium ferrocyanide is a double-layer carbon-coated sodium ferrocyanide, comprising sodium ferrocyanide and a first carbon layer and a second carbon layer sequentially coated on the outside of the sodium ferrocyanide.

3. The battery separator according to claim 2, characterized in that: The carbon source for forming the first carbon layer includes at least one of polyvinyl alcohol, glacial acetic acid, tannic acid and oxalic acid.

4. The battery separator according to claim 2, characterized in that: The carbon source for forming the second carbon layer includes sorbitan monooleate polyoxyethylene ether.

5. The battery separator according to claim 2, characterized in that: The preparation method of the carbon-coated sodium ferrocyanide comprises the following steps: Sodium ferrocyanide is mixed with the carbon source of the first carbon layer, ethanol is added dropwise for grinding, and the material after grinding is subjected to a first drying treatment. The material after the first drying treatment is then mixed with the carbon source of the second carbon layer, ethanol is added dropwise for grinding, and the material after grinding is subjected to a second drying treatment. The material after the second drying treatment is carbonized under an inert atmosphere to obtain double-layer carbon-coated anhydrous sodium ferrocyanide.

6. The battery separator according to claim 5, characterized in that: The sodium ferrocyanide is anhydrous sodium ferrocyanide obtained by grinding and drying sodium ferrocyanide decahydrate; The mass ratio of the carbon source of the first carbon layer to the anhydrous sodium ferrocyanide is 2%-8%; and / or the mass ratio of the carbon source of the second carbon layer to the anhydrous sodium ferrocyanide is 1%-5%.

7. The battery separator according to claim 5, characterized in that: The temperature of the carbonization treatment is 260-300° C., and the time of the carbonization treatment is 6-10 hours.

8. The battery separator according to claim 1, characterized in that: Contains at least one of the following characteristics: (1) In terms of mass percentage, the coating comprises 70%-90% of the carbon-coated sodium ferrocyanide, 5%-20% of the conductive agent, and 5%-10% of the binder; (2) The binder includes PVDF and / or CMC; (3) The thickness of the coating is 5-30 μm.

9. The method for preparing a battery separator according to any one of claims 1 to 8, characterized in that: The following steps are involved: The carbon-coated sodium ferrocyanide, a conductive agent, a binder and a solvent are mixed to form a slurry, which is then coated on a diaphragm substrate and dried to obtain the slurry.

10. An aqueous sodium ion battery, characterized in that: A battery separator comprising the battery separator according to any one of claims 1 to 8 or a separator prepared by the method for preparing a battery separator according to claim 9.

Citation Information

Patent Citations

  • Carbon coating method of sodium ferrocyanide material for sodium ion battery

    CN114725384A

  • Preparation method of cobalt-free ternary positive electrode material and lithium ion battery

    CN115818735A

  • Negative electrode for non-aqueous electrolyte secondary battery, separator for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery

    CN117099224A

  • Composite diaphragm for sodium-ion battery as well as preparation method and application of composite diaphragm

    CN117638403A

  • Diaphragm, preparation method thereof and aqueous sodium ion battery

    CN117832756A

Cited By

  • Sodium-ion battery positive electrode sodium supplementing additive and preparation method and application thereof

    CN119994067A

  • Protective layer, sodium ion battery, power utilization device and preparation method of protective layer

    CN121439929A